Economic and legal differences in patterns of land use in Ukraine - Федчишин, Дмитро Володимирович; Федчишин, Д. В.; Федчишин, Дмитрий Владимирович; Fedchyshyn, Dmytro V.; Ігнатенко, Ірина Володимирівна; Ігнатенко, І. В.; Игнатенко, Ирина Владимировна; Ihnatenko, Iryna V.; Швидка, Вікторія Георгіївна; Швидка, В. Г.; Швыдка, Виктория Георгиевна; Shvydka, Viktoriia H.; et al. (Editorial Primmate S. A. S., 2019)
The article deals with the legal patterns of the use of agricultural land in Ukraine. Legislative consolidation of the moratorium on the alienation of agricultural land leads to a search for legal ways of investors' access to land use in Ukraine. The methodological basis of the study was a complex of philosophical (dialectical, systemic-structural) and special legal (formally-logical, comparative-legal, forecasting and method of interpretation) methods of scientific knowledge. The Agreement of land lease and the agreement of emphyteusis are considered as the object of the study. It is determined that land lease is the most widespread pattern of use of agricultural land. Land lease performs social functions, creating conditions for access to land resources of those who do not own them, and provides conditions for entrepreneurship in the field of agriculture. The authors also consider emphyteusis, which is the right to use the land for agricultural purposes, as well as its features. The article analyzes the differences between lease and emphyteusis in order to determine the most cost-effective and environmentally safe pattern of land use for agricultural entities in modern conditions. In the content of the work, the authors substantiate that the agreement of emphyteusis has certain advantages over the lease agreement. The authors come to the conclusion that emphyteusis can be also considered as an alternative to purchase and selling of land under the moratorium on the alienation of agricultural land in Ukraine.

У статті розглядаються правові закономірності використання земель сільськогосподарського призначення в Україні. Законодавче закріплення мораторію на відчуження земель сільськогосподарського призначення веде до пошуку легальних шляхів доступу інвесторів до землекористування в Україні. Методологічною основою дослідження став комплекс філософських (діалектичних, системно-структурних) та спеціально-правових (формально-логічний, порівняльно-правовий, прогнозний та метод інтерпретації) методів наукового пізнання. Об'єктом дослідження розглядаються договір оренди землі та договір емфітевзису. Визначено, що оренда землі є найбільш поширеною формою використання земель сільськогосподарського призначення. Оренда землі виконує соціальні функції, створюючи умови для доступу до земельних ресурсів тих, хто ними не володіє, та забезпечує умови для підприємництва у сфері сільського господарства. Також автори розглядають емфітевзис, що є правом користування землею для сільськогосподарських потреб, а також його особливості. У статті проаналізовано відмінності між орендою та емфітевзисом з метою визначення найбільш економічно ефективної та екологічно безпечної схеми землекористування для сільськогосподарських суб’єктів у сучасних умовах. У змісті роботи автори обґрунтовують, що договір емфітевзису має певні переваги перед договором оренди. Автори приходять до висновку, що емфітевзис також можна розглядати як альтернативу купівлі-продажу землі за умов мораторію на відчуження земель сільськогосподарського призначення в Україні.
Fedchyshyn D. Economic and legal differences in patterns of land use in Ukraine / D. Fedchyshyn, I. Ignatenko, V. Shvydka // Amazonia Investiga. – Vol. 8. – Iss. 18. – Editorial Primmate S. A. S., 2019. – P. 103-110.
Keywords: land lease; emphyteusis; land use; agricultural land; land plot; civil law; land law; оренда землі; емфітевзис; землекористування; землі сільськогосподарського призначення; земельна ділянка; цивільне право; земельне право; Research Subject Categories::LAW/JURISPRUDENCE